1996
DOI: 10.1007/s002560050032
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of normal patellar cartilage volume and thickness using MRI: an analysis of currently available pulse sequences

Abstract: The FLASH and fat-suppressed FLASH sequences allowed the most accurate determination of the cartilage volume and thickness. Fat-suppression considerably increased the contrast of the cartilage to the synovial fluid, fat and bone marrow, yielding higher reproducibility of the volumetric measurements. The remaining difference from the anatomical volume and thickness may be because the calcified cartilage is not delineated by magnetic resonance imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 21 publications
1
66
0
2
Order By: Relevance
“…Recent advances in MRI technology have led to significant improvements in spatial resolution and contrast, enabling researchers to evaluate anatomic damage of all these joint structures in the axial, coronal, and sagittal planes (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Recently, we and other investigators have developed a system for quantifying cartilage volume using MRI acquisitions combined with sophisticated software (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41); however, to date, few studies have used MRI technology to evaluate cartilage volume changes over time (42)(43)(44)(45)(46).…”
mentioning
confidence: 99%
“…Recent advances in MRI technology have led to significant improvements in spatial resolution and contrast, enabling researchers to evaluate anatomic damage of all these joint structures in the axial, coronal, and sagittal planes (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Recently, we and other investigators have developed a system for quantifying cartilage volume using MRI acquisitions combined with sophisticated software (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41); however, to date, few studies have used MRI technology to evaluate cartilage volume changes over time (42)(43)(44)(45)(46).…”
mentioning
confidence: 99%
“…MR imaging can delineate the cartilage with highresolution and high contrast to surrounding tissue, provided that fat-suppressed gradient-echo sequences are employed [30,34,37]. In the knee, which displays cartilage thickness values of 5 mm and more, it has been shown that the cartilage volume can be determined with a high degree of accuracy [9,11,12,27,30,33].…”
mentioning
confidence: 99%
“…Specific 3D digital image analysis techniques have also permitted to compute the cartilage thickness and its variation throughout knee joint cartilage plates [5,38,39]. These analyses have been validated in comparison with anatomical sectioning [9,37], CT arthrography [I 1,121, A-mode ultrasound [S], and stereophotogrammetry [5]. The precision (reproducibility) of these measurements has also been examined under clinical in vivo imaging conditions, revealing coefficients of variation between 1% and 4% for estimates of cartilage volume and mean thickness [ 10,13,2 1,24, 30,39,43].…”
mentioning
confidence: 99%
“…In the patella specimen, less than 17% of the image points deviated more than 0.5 mm when comparing MRI and histological sections. Between 50% and 90% were within an interval of 0.5 mm [19]. In our study, a difference of 0.5 mm would have led to a possible difference of about 20% for the average cartilage thickness of 2.69 mm.…”
Section: Discussionmentioning
confidence: 41%